RISK FACTORS ASSOCIATED WITH SPONTANEOUS ABORTION AT DR. SOETOMO HOSPITAL IN 2019–2023 - Sabrina, Rania; Aprilawati, Dwi; Dwiningsih, Sri Ratna (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Spontaneous abortion or miscarriage is one of the pregnancy complications which can cause vaginal bleeding, as well as a significant impact on women's psychology. The occurrence of spontaneous abortion is caused by several risk factors that need to be considered. This research is aimed to analyze risk factors related to spontaneous abortion in pregnant women at Dr. Soetomo Hospital. Method: The study used a cross-sectional approach. The population was women who checked their pregnancy at Dr. Soetomo Hospital who experienced spontaneous abortion and did not experience spontaneous abortion. The number of samples was 55 for the case group and 55 for the control group. Data were obtained from medical records at Dr. Soetomo Hospital Surabaya. Bivariate chi-square statistical analysis and multivariate logistic regression were performed using SPSS software. Results: The risk factors found to be significant for the occurrence of spontaneous abortion were maternal age (p = 0.003), pregnancy interval (p = 0.005), and hemoglobin levels (p = 0.005). Meanwhile, the insignificant risk factors for the occurrence of spontaneous abortion were parity (p = 0.070) and body mass index (p = 0.525). The most dominant risk factor associated with the occurrence of spontaneous abortion was maternal age <20 or >35 years (OR = 6,769). Conclusion: maternal age, pregnancy interval, and hemoglobin level have been shown to be the significant risk factors for spontaneous abortion in pregnant women.